PENGARUH PEMAHAMAN AKUNTANSI, PEMAHAMAN KETENTUAN PERPAJAKAN DAN TRANSPARANSI DALAM PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN - Yunita Eriyanti Pakpahan; Hardi -; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of an understanding of accounting, an understanding of taxation provisions, and transparency in tax. The data collecting method used in this research is survey method by means of questionnaire instrument directly delivered to respondents in tax and accountant division who reporting annual tax return to KPP Madya. A total of 92 respondents (92%) collected and used in the analysis. Methods of analysis used in this study is the technique of multiple regression analysis version 20.0. Result of the study showed that the variables understanding of accounting, understanding of taxation provisions, and transparency in tax effect on taxpayers compliance agency in KPP Madya Pekanbaru. The magnitude of the effect caused by Adjusted R2 by three variables together 54.4% of the dependent variable, while the remaining 45.6% is influenced by other variables not examined in this study.Keywords: Taxpayers compliance agency, understanding of accounting, understanding of taxation provisions, and transparency in tax.